Role of Recipient Susceptibility Factors During Contact-Dependent Interbacterial Competition - Lin, Hsiao-Han; Filloux, Alain; Lai, Erh-Min (Frontiers in Microbiology, 2020)
Bacteria evolved multiple strategies to survive and develop optimal fitness in their ecological niche. They deployed protein secretion systems for robust and efficient delivery of antibacterial toxins into their target cells, therefore inhibiting their growth or killing them. To maximize antagonism, recipient factors on target cells can be recognized or hijacked to enhance the entry or toxicity of these toxins. To date, knowledge regarding recipient susceptibility (RS) factors and their mode of action are mostly originating from studies on the type Vb secretion system that is also known as the contact-dependent inhibition (CDI) system. Yet, recent studies on the type VI secretion system (T6SS), and the contact-dependent inhibition by glycine-zipper protein (Cdz) system, also reported the emerging roles of RS factors in interbacterial competition. Here, we review these RS factors and their mechanistic impact in increasing susceptibility of recipient cells in response to CDI, T6SS, and Cdz. Past and future strategies for identifying novel RS factors are also discussed, which will help understanding the interplay between attacker and prey upon secretion systems-dependent competition. Understanding these mechanisms would also provide insights for developing novel antibacterial strategies to antagonize aggressive bacteria-killing pathogens.